1993
DOI: 10.1200/jco.1993.11.9.1717
|View full text |Cite
|
Sign up to set email alerts
|

S-phase fraction is a prognostic factor in stage I breast carcinoma.

Abstract: This study suggests that cytometric SPF has prognostic significance in stage I breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
4

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 36 publications
3
26
0
4
Order By: Relevance
“…In this view, it is promising that a high proportion of relapses in systemically untreated premenopausal patients seems to be identified by S-phase fraction (Stal et al, 1992). Recently, we also reported results suggesting that SPF is a long-term prognostic factor in small node-negative tumours (T1NO) (Stal et al, 1993). These results, together with the present data, suggest that estimation of proliferative activity could facilitate the identification of early breast cancer patients suitable for adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 66%
“…In this view, it is promising that a high proportion of relapses in systemically untreated premenopausal patients seems to be identified by S-phase fraction (Stal et al, 1992). Recently, we also reported results suggesting that SPF is a long-term prognostic factor in small node-negative tumours (T1NO) (Stal et al, 1993). These results, together with the present data, suggest that estimation of proliferative activity could facilitate the identification of early breast cancer patients suitable for adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies in which cell kinetics have been determined using the in vitro (3H) thymidine labeling index [1,2] or flow cytometric evaluation of the S-phase fraction (SPF) of the cell cycle [3,4], demonstrated that these markers have an independent prognostic val-ue in series of node-negative breast cancer (NNBC) patients. However, both these methods present some technical difficulties, are complex, and timeconsuming, and have not yet been completely standardized [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many studies found that S-phase and DNA ploidy were highly correlated. When tested in multivariate analysis strategies, DNA ploidy failed to be an independent prognostic variable (26,27). Also, some investigators presented data that failed to show any prognostic significance of either S-phase (28 -30) or DNA ploidy (28,30,31).…”
mentioning
confidence: 99%